2017
DOI: 10.1007/s00192-017-3400-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonbiologic factors that impact management in women with urinary incontinence: review of the literature and findings from a National Institute of Diabetes and Digestive and Kidney Diseases workshop

Abstract: NBFs that potentially affect the UI management pathway are not well understood, and a comprehensive, interdisciplinary approach to research is needed to understand and appropriately support effective UI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 105 publications
3
25
0
2
Order By: Relevance
“…Anecdotally, there was a strong preference for ambiguous and positive names that included the word “health” in the free‐text question. Our study is consistent with the current literature, as it demonstrates an attitude of shame and embarrassment towards female pelvic disorders which likely prevents patients from seeking appropriate care . Interestingly, we found that despite societal stigma, our cohort expressed a relatively high comfort level discussing incontinence with a physician.…”
Section: Discussionsupporting
confidence: 90%
“…Anecdotally, there was a strong preference for ambiguous and positive names that included the word “health” in the free‐text question. Our study is consistent with the current literature, as it demonstrates an attitude of shame and embarrassment towards female pelvic disorders which likely prevents patients from seeking appropriate care . Interestingly, we found that despite societal stigma, our cohort expressed a relatively high comfort level discussing incontinence with a physician.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on UI commonly report that having a lower educational attainment poses an increased risk of leaking urine due to lack of awareness . Another review showed that cohorts with higher educational level are more likely to seek care for their UI symptoms . Our results suggest that those with lower educational attainment may have lower prevalence due to lack of awareness and delay in reporting these symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…21 Another review showed that cohorts with higher educational level are more likely to seek care for their UI symptoms. 22 Our results suggest that those with lower educational attainment may have lower prevalence due to lack of awareness and delay in reporting these symptoms. This in turn would explain why those who have more frequent urine leakage have lower educational attainment, since the delay in seeking help may have resulted in a more severe form of leakage.…”
Section: Socio-demographics (Age Education Employment Status Ancmentioning
confidence: 71%
“…1,3,8,9 Furthermore, PFD affects wo-menʼs QoL, with significant increases in depression, embarrassment, and social isolation, as highlighted in the selected studies, with the impact on different aspects of life contributing to the growing socioeconomic and health problems of PFD for society. 8,28 Therefore, PFD, either alone or combined, has been studied in specific populations that present greater risk, such as women, older adults, and nursing staff. Studies concerning the investigation of the prevalence and impact of LUTS may contribute to improve health promotion and the quality of the care provided to the most affected groups, such as women, who, according to some findings, are affected by UI in a proportion of two to one in relation to men.…”
Section: Iciqui-sfmentioning
confidence: 99%